Involvement of thoracal spine and paraspinal abscesses due to brucellosis - Pekdemir, Hasan; Buyukberber, Suleyman; Kaygusuz, Akif; Baysal, Tamer; Ak, Gursel; Gurer, Inanc; Buyukberber, Nuray (Annals of Medical Research, 2021)
None
Keywords: s : Brucellosis, thoracal spine, paraspinal abscesses